EFFECT OF AUDIO-VISUAL HEALTH EDUCATION ON PSYCHOLOGICAL DISTRESS OF PERIOPERATIVE PATIENTS: A SYSTEMATIC REVIEW - Setiawan, Arif; Sriyono; Maryanti, Herdina (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Audiovisual health education for postoperative patients is a strategy used by health care providers to reduce psychological distress in postoperative patients. Health education improves the patient's adaptation to the anxiety associated with a surgical project. Methods: This study was a systematic review study of 4 databases, namely Web of Science, PubMed, EBSCO Host, and Scopus, with keywords “Audio-Visual" OR "Health Education" AND "Psychological Distress" OR "Perioperative" OR "Surgery. The result followed the protocol and rules of Preferred Reporting Items for Systematic Review (PRISMA) and used JBI tools to assess the quality of articles to be analyzed. The inclusion criteria in this study were articles that taken in the last 5 years with the method of Randomized Control Trials (RCTs). Results: The literature search resulted in 2324 research articles, of which 10 were included after multiple selections in the systematic review and were eligible for analysis. All 10 articles used the randomization comparison research method. Most of the articles showed a positive impact on perioperative patient anxiety either with audiovisual intervention alone or in combination. Conclusion: It showed that health education with audiovisual assistance is one of the effective educational methods to increase knowledge to reduce perioperative patient distress. Therefore, audiovisual health education should be implemented to improve patient satisfaction and job effectiveness.